A colloidal heterostructured quantum dot sensitized carbon nanotube–TiO2 hybrid photoanode for high efficiency hydrogen generation. Issue 2 (16th November 2018) - Selopal, Gurpreet Singh; Mohammadnezhad, Mahyar; Navarro-Pardo, Fabiola; Vidal, François; Zhao, Haiguang; Wang, Zhiming M.; Rosei, Federico
Abstract : A photoelectrochemical device based on a TiO2 /QD–MWCNT (0.015 wt%) hybrid photoanode yields 40% higher photocurrent density than the control device. Abstract : Solar-driven photoelectrochemical (PEC) hydrogen (H2 ) generation is a promising approach to harvest solar energy for the production of a clean chemical fuel. However, the low photon-to-fuel conversion efficiency and long-term stability of PEC devices are major challenges to be addressed to enable large-scale commercialization. Here we report a simple, fast and cost-effective approach to fabricate high efficiency and stable PEC devices for H2 generation, by fabricating a hybrid photoanode obtained by incorporating small amounts of multiwall carbon nanotubes (MWCNTs) into a TiO2 mesoporous film and sensitizing with colloidal heterostructured CdSe/(CdSe x S1− x )5 /(CdS)2 quantum dots (QDs). The latter were specially designed to accelerate the exciton separation through a band engineering approach. The PEC devices based on the TiO2 /QD–MWCNT (T/Q–M) hybrid photoanode with an optimized amount of MWCNTs (0.015 wt%) yield a saturated photocurrent density of 15.90 mA cm −2 (at 1.0 V RHE ) under one sun illumination (AM 1.5G, 100 mW cm −2 ), which is 40% higher than that of the reference device based on TiO2 /QD (T/Q) photoanodes. This is attributed to a synergistic effect of the promising optoelectronic properties of the colloidal heterostructured QDs and improved electron transport (reduced charge transfer resistance) within the TiO2 –MWCNT hybrid anodes enabled by the directional path of MWCNTs for the photo-injected electrons towards FTO. Furthermore, the PEC device based on the T/Q–M hybrid photoanode is more stable (∼19% loss of its initial photocurrent density) when compared with the T/Q photoanode (∼35% loss) after two hours of continuous one sun illumination. Our results provide fundamental insights and a different approach to improve the efficiency and long-term stability of PEC devices and represent an essential step towards the commercialization of this emerging solar-to-fuel conversion technology.